Human Capital Analytics and Employee Well-being: The Role of Artificial Intelligence in Improving Organizational Performance - Prastiyo Diatmono (Nomico, 2026)
The rapid diffusion of artificial intelligence (AI) into human resource management has repositioned human capital analytics (HCA) as a strategic lever for employee well-being and organizational performance. This article synthesizes empirical and conceptual literature published between 2021 and 2026 to examine how AI-enabled HCA practices, covering predictive workforce analytics, AI-driven engagement monitoring, and intelligent decision-support systems, shape employee well-being and, in turn, organizational performance. Using a systematic literature review method following the PRISMA protocol, twenty-five peer-reviewed sources retrieved from Google Scholar-indexed databases were analyzed thematically. Findings indicate that AI-supported HCA improves workforce planning accuracy, reduces administrative workload, and enables personalized well-being interventions, although effectiveness remains contingent on transparent governance, ethical data use, and supportive leadership. The review identifies an underexplored mediating pathway in which psychological safety and perceived organizational support connect AI-driven HCA to well-being and performance outcomes, a gap inadequately addressed in models that treat AI adoption as a direct performance driver. The article proposes an integrative conceptual framework linking human capital analytics, AI capability, employee well-being, and organizational performance, offering theoretical contribution to human resource management scholarship and practical guidance for organizations deploying AI responsibly within people analytics functions.